2017
DOI: 10.1002/ptr.5799
|View full text |Cite
|
Sign up to set email alerts
|

A Polyphenol‐rich Pomegranate Fruit Extract Suppresses NF‐κB and IL‐6 Expression by Blocking the Activation of IKKβ and NIK in Primary Human Chondrocytes

Abstract: Pomegranate fruit extract (PE) rich in polyphenols have been shown to exert chondroprotective effects but the mechanism is not established. Here, we used an in vitro model of inflammation in OA to investigate the potential of PE to suppress IL-1β-stimulatedexpression of inflammatory cytokine IL-6, generation of reactive oxygen species (ROS) levels and investigated the mechanism of NF-κB inhibition by analyzing the activation of the kinases upstream of IκBα in primary human chondrocytes. Total and phosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
(29 reference statements)
2
25
0
Order By: Relevance
“…Efficiency of notochordal differentiation was analyzed by determining the percent positive cell population for the notochordal markers. Twenty thousand cells in each group were acquired using BD‐fluorescence‐activated cell sorting (FACS) Aria II (BD Biosciences) and data were analyzed using FlowJo software from Tree Star, Inc. (Ashland, OR) as described previously (Haseeb, Khan, Ashruf, & Haqqi, ; Khan, Ahmad, Ansari, & Haqqi, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficiency of notochordal differentiation was analyzed by determining the percent positive cell population for the notochordal markers. Twenty thousand cells in each group were acquired using BD‐fluorescence‐activated cell sorting (FACS) Aria II (BD Biosciences) and data were analyzed using FlowJo software from Tree Star, Inc. (Ashland, OR) as described previously (Haseeb, Khan, Ashruf, & Haqqi, ; Khan, Ahmad, Ansari, & Haqqi, ).…”
Section: Methodsmentioning
confidence: 99%
“…(Ashland, OR) as described previously (Haseeb, Khan, Ashruf, & Haqqi, 2017;Khan, Ahmad, Ansari, & Haqqi, 2017).…”
Section: Flow Cytometry To Determine the Efficiency Of Notochordal mentioning
confidence: 99%
“…When the NF-κB signaling pathway is blocked, the expression of TNF-α and IL-6 is downregulated. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…In this context, we recently demonstrated that the leaf hydroalcoholic extract obtained from pomegranate is anti-inflammatory as it inhibits TNF- α production and decreases neutrophil migration in a rat model of lipopolysaccharide- (LPS-) induced acute peritonitis [ 8 ]. Furthermore, Haseeb et al showed that the pomegranate fruit extract attenuates IL-6 production, reactive oxygen species, IL-1 β -mediated phosphorylation of the inhibitor of nuclear factor kappa-B kinase subunit beta (IKK β ), expression of IKK β mRNA, degradation of I κ B α , and the activation and nuclear translocation of NF- κ B/p65 in human chondrocytes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%